2018
DOI: 10.1530/joe-17-0708
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptor localization in target tissues

Abstract: The thyroid hormone receptors, TRα1, TRβ1 and other subtypes, are members of the nuclear receptor superfamily that mediate the action of thyroid hormone signaling in numerous tissues to regulate important physiological and developmental processes. Their most well-characterized role is as ligand-dependent transcription factors; TRs bind thyroid hormone response elements in the presence or absence of thyroid hormone to facilitate the expression of target genes. Although primarily residing in the nucleus, TRα1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 147 publications
2
67
0
9
Order By: Relevance
“…Links between BC and expression of other NR have already been outlined by our lab and others [5][6][7][8][9][10]. Thyroid hormone receptors (THR) are members of the NR superfamily that mediate the classical genomic actions of thyroid hormone (TH) signaling in numerous tissues and regulate important physiological and developmental processes [11,12]. THR primarily act as ligand-dependent transcription factors, after heterodimerization with retinoid X receptor (RXR).…”
Section: Introductionmentioning
confidence: 99%
“…Links between BC and expression of other NR have already been outlined by our lab and others [5][6][7][8][9][10]. Thyroid hormone receptors (THR) are members of the NR superfamily that mediate the classical genomic actions of thyroid hormone (TH) signaling in numerous tissues and regulate important physiological and developmental processes [11,12]. THR primarily act as ligand-dependent transcription factors, after heterodimerization with retinoid X receptor (RXR).…”
Section: Introductionmentioning
confidence: 99%
“…Our prior studies have shown that in HeLa cells overexpression of wild-type TR does not saturate the capacity of the nuclear import machinery, nor do fluorescent protein tags alter localization patterns. Further, wild-type TR is primarily nuclear over a wide range of expression levels in transfected cells, 31,[35][36][37]65 and supports T 3 -dependent gene transactivation in reporter assays. 69 Finally, distribution patterns of exogenous TRs in HeLa cells are the same as in cell lines that express endogenous TRs, including HepG2 (hepatocellular carcinoma) cells that express low levels of TRα1 and TRβ1, and GH4C1 (rat pituitary tumor) cells that express high levels of both TRα1 and TRβ1.…”
Section: Overexpression Of Med1 Increases Nuclear Retention Of Trβ1mentioning
confidence: 72%
“…[21][22][23] Transcription factors, such as TRα1 and TRβ1, cross the nuclear envelope through the nuclear pore complexes, facilitated by transport proteins called importins and exportins. [24][25][26][27][28][29][30] Although localized primarily to the nucleus at steady-state, TRα1 and TRβ1 shuttle between the nucleus and cytosol, directed by multiple nuclear export signal (NES) and nuclear localization signal (NLS) motifs [31][32][33][34] ( Figure 1A). Along with a NLS in the hinge domain (NLS-1), TRα1 houses a NLS in the A/B domain that is absent in TRβ1 and inactive in the retroviral oncoprotein v-ErbA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Перебіг цієї реакції відбувається у середині молекули тиреоглобуліну і призводить до утворення різних йодтиронінів, включаючи тироксин (Т 4) і трийодтиронін (Т 3 ). Значна частина тиреоглобуліну зберігається в залозі, відіграючи роль прогормона [5].…”
unclassified